Production of medium chain length polyhydroxyalkanoates from waste oils by recombinant Escherichia coli. Issue 7 (24th July 2015) - Vastano, Marco; Casillo, Angela; Corsaro, Maria Michela; Sannia, Giovanni; Pezzella, Cinzia
<x xml:space="preserve">Abstract</x> Medium chain length polyhydroxyalkanoates (mcl‐PHAs) are attractive "green" alternatives to conventional petroleum‐based plastics, finding application in various fields. However, their sustainable exploitation is still hampered by the high production costs. In this work, an Escherichia coli recombinant system has been designed to allow accumulation of mcl‐type polymers through conversion of waste materials, such as spent cooking oils. The system has been engineered with a newly isolated PHAs biosynthetic operon from Bacillus cereus 6E/2 and tested for PHAs production on different carbon sources. Results have highlighted the peculiar specificity of the designed E. coli system to drive the incorporation of 3‐hydroxyhexanoate monomers (up to 99%) in produced PHAs, whatever is the related C‐source fed to the growth medium: fatty acids with different length, vegetable oils, or complex waste oils. The work also provides first clues about the role played by B. cereus PHA biosynthetic proteins in PHA production process, laying the basis for the development of ad hoc designed cell factories for the synthesis of polymers with defined composition.